Pengembangan Produk Funding Dengan Akad Musyarakah Pada Bank Syariah - Trimulato, Trimulato (Falah: Jurnal Ekonomi Syariah, 2017)
The rapid development of shariah banking in Indonesia can be seen by its market share which exceeded 5 percent nationally in 2016. Furthermore, the shariah banking have a strong legal law with the presence of the law number 21 of 2008. Total deposits in shariah banking reached 240,974,000,000,000. To increase public interest to choose shariah banking have to innovate in both product funding and product financing. Musharakah contract is currently only used on product financing, weather has not been used in the funding product. This paper uses a descriptive qualitative method, this paper is focused on raising funding products by musharakah contract. To increase the volume of funding products, syariah banking need to use musharakah contract on funding products. The results of this paper concluded that, in the period of December 2015 through December 2016 the musharakah contract on financing products increased up to 29.17 percent. Musyarakah contract has not been used on funding products. Both musharakah and mudarabah have the same pattern as the model for the results. While mudharabah used in funding products, musharakah can also be used for funding products in shariah banking. The Development of funding product with musharakah contract in shariah banking will be profitable for banks and customers. It will be more easily raise money to meet the large volume of financing, then the Musharakah agreement will provide for more great results for customers.